2017
DOI: 10.1186/s12913-017-2163-x
|View full text |Cite
|
Sign up to set email alerts
|

A questionnaire measuring staff perceptions of Lean adoption in healthcare: development and psychometric testing

Abstract: BackgroundDuring the past decade, the concept of Lean has spread rapidly within the healthcare sector, but there is a lack of instruments that can measure staff’s perceptions of Lean adoption. Thus, the aim of the present study was to develop a questionnaire measuring Lean in healthcare, based on Liker’s description of Lean, by adapting an existing instrument developed for the service sector.MethodsA mixed-method design was used. Initially, items from the service sector instrument were categorized according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 36 publications
1
32
0
2
Order By: Relevance
“…Acceptability: consumer = 10 [23,37,39,41,42,44,51,52,57,59], provider = 27 [24-36, 38, 40, 43, 45-50, 53-56, 58] Appropriateness: consumer = 3 [61][62][63], provider = 3 [46,60,64], both consumer and provider = 1 [65] Adoption: consumer = 1 [66], provider = 3 [67][68][69] Feasibility: provider = 4 [46,70,71,80] Penetration: organisation = 4 [72][73][74][75] Sustainability: provider = 2 [76,77], organisation = 2 [78,79] Methodological quality Table 1 presents the global COSMIN scores for reliability, validity and responsiveness, and rank orders the instruments by descending reliability scores. Detailed COSMIN scores for individual measurement properties are presented in Additional file 3.…”
Section: Selection Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Acceptability: consumer = 10 [23,37,39,41,42,44,51,52,57,59], provider = 27 [24-36, 38, 40, 43, 45-50, 53-56, 58] Appropriateness: consumer = 3 [61][62][63], provider = 3 [46,60,64], both consumer and provider = 1 [65] Adoption: consumer = 1 [66], provider = 3 [67][68][69] Feasibility: provider = 4 [46,70,71,80] Penetration: organisation = 4 [72][73][74][75] Sustainability: provider = 2 [76,77], organisation = 2 [78,79] Methodological quality Table 1 presents the global COSMIN scores for reliability, validity and responsiveness, and rank orders the instruments by descending reliability scores. Detailed COSMIN scores for individual measurement properties are presented in Additional file 3.…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…Twelve (12/65) scales scored 7 or more (of the maximum possible score = 22), indicating greater psychometric strength on the ConPsy checklist [23,45,46,61,69,[76][77][78]. Detailed ConPsy scores for each scale are presented in Additional file 4.…”
Section: Psychometric Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…If integrated with other organizational processes, ProMES can give employees some control over assessment and monitoring, thereby possibly mitigating some of the negative effects of new public management and achieving less stress and more “dignity” [ 42 ]. However, the Swedish health care system has, during the past decade, implemented lean thinking with the aim to improve quality of care and increase efficiency [ 43 ]. In other words, a lot of measuring besides that initiated through working with ProMES was taking place during the study and it is unclear how these two processes interacted with each other.…”
Section: Discussionmentioning
confidence: 99%
“…[17] Studies on the implementation of Lean principles in healthcare have been limited and there are few studies that considered the consequences of Lean on healthcare workers' perceptions of Lean. [18] Also, there is a lack of in-depth research on Lean readiness. Researchers and practitioners have shown that, despite the benefits that Lean can offer to organizations, there have been a large number of failed implementations of it.…”
Section: Introductionmentioning
confidence: 99%